Analysis of local strain in aluminium interconnects by energy filtered CBED - Krämer, S.; Mayer, J.; Witt, C.; Weickenmeier, A.; Rühle, M. (Ultramicroscopy, 2000)
Energy filtered convergent beam electron diffraction (CBED) was used to investigate localised strain in aluminium interconnects. The quantitative analysis of the experimental patterns is based on a multi-step evaluation procedure which is the main subject of the present paper. The improvements which were made to the analysis method aim at increasing both the automation and the accuracy. The detection of the higher order Laue zone (HOLZ) line positions is performed by means of the Hough transform. The required sub-pixel resolution can be achieved routinely and the achievable accuracy is only limited by the line width and the amount of noise in the patterns. The determination of the strain state is performed via a refinement algorithm which is based on varying the strain state in the sample coordinate system and simulating the patterns for the individual grains until a best fit with the experiment is obtained. For the simulation we have developed a new correction scheme in which the dynamical effects are treated separately for each individual HOLZ line. The results show that the main source of the observed strains is the difference in thermal expansion coefficients. The strain is substantially reduced underneath a hillock in the interconnect. Asymmetries in the strain distribution around the hillock show that the unidirectional diffusion during electromigration tests causes peak strains in areas next to the hillock which may be possible failure sites.